2020
DOI: 10.1042/bsr20192121
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharide attenuates metabolic memory-triggered ER stress and apoptosis via regulation of miR-204/SIRT1 axis in retinal pigment epithelial cells

Abstract: Background: ‘Metabolic memory’ of early hyperglycaemic environment has been frequently suggested in the progression of diabetic retinopathy (DR). Retinal pigment epithelial (RPE) cells are crucial targets for DR initiation following hyperglycaemia. Astragalus polysaccharides (APS) has been long used as a traditional Chinese medicine in treating diabetes. In the present study, the preventive effects and mechanisms of APS on metabolic memory-induced RPE cell death were investigated. Methods: The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
1
23
1
Order By: Relevance
“…It has been suggested that sepsis is related to endoplasmic reticulum activation, that is, the disorder of intracellular homeostasis caused by sepsis can destroy the homeostasis of the endoplasmic reticulum, thereby causing ERS [ 25 , 27 ]. Previous studies have found that APS can inhibit ERS by regulating the miR-204/SIRT1 axis of retinal pigment epithelial cells [ 28 ]. The results of this study show that LPS can induce ERS in HK-2 cells and increase the expression of ERS-related markers CHOP and GRP78, while APS pretreatment inhibited the increase of mRNA and protein expression of CHOP and GRP78 in HK-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that sepsis is related to endoplasmic reticulum activation, that is, the disorder of intracellular homeostasis caused by sepsis can destroy the homeostasis of the endoplasmic reticulum, thereby causing ERS [ 25 , 27 ]. Previous studies have found that APS can inhibit ERS by regulating the miR-204/SIRT1 axis of retinal pigment epithelial cells [ 28 ]. The results of this study show that LPS can induce ERS in HK-2 cells and increase the expression of ERS-related markers CHOP and GRP78, while APS pretreatment inhibited the increase of mRNA and protein expression of CHOP and GRP78 in HK-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These effects have been shown to occur in animal models as well as in cell culture models. Cells isolated from diabetic donor retinas or animal models retain their diabetic metabolic phenotype for several passages [40][41][42][43][44][45]. Human control and diabetic donor cells were previously shown to display metabolic memory characteristics right after the isolation and for up to eight passages [40].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that ER stress contributes to endothelial cell inflammatory responses and apoptosis in diabetic retinopathy [ 95 , 96 ]. In streptozotocin (STZ)-induced type 1 diabetic mice, retinal inflammation and vascular leakage are attributed to ATF4 activation of STAT3 [ 97 , 98 ].…”
Section: Er Stress Linking To Cardiovascular Complications In Diabetes and Obesitymentioning
confidence: 99%